Kadar Protein, Beta Karoten, dan Serat Pangan Makanan Pendamping Air Susu Ibu dengan Substitusi Glukomanan Berbahan Lele (Clarias gariepinus), Tempe, dan Labu Kuning (Cucurbita pepo) : Kadar Protein, Beta Karoten, dan Serat Pangan Makanan Pendamping Air Susu Ibu dengan Substitusi Glukomanan Berbahan Lele (Clarias gariepinus), Tempe, dan Labu Kuning (Cucurbita pepo) - Kurnia Putri Ingge; Veriani Aprilia; Pramitha Sari (Universitas Airlangga, 2026)
Background: Stunting is a condition in which a child fails to thrive, particularly among malnourished toddlers during the first thousand days of life. Local complementary food (MPASI) can be made from ingredients available in the child’s living area. It is administered to kids aged six to twenty-four months to increase their appetite. Objectives: To evaluate the effect of porang (Amorphophallus oncophyllus) glucomannan substitution on the protein, beta-carotene, and dietary fiber content of local complementary food from catfish (Clarias gariepinus), tempe, and pumpkin (Cucurbita pepo) (Letelaku). Methods: This was experimental research employed a completely randomized design (CRD). MPASI porridge was made from catfish, tempeh, and pumpkin. Glucomannan substitution was applied to rice flour at concentrations of 30% (F1), 40% (F2), and 50% (F3). Beta-carotene levels were analyzed using the spectrophotometric method, dietary fiber content using the multienzyme method, and protein content using the Kjeldahl method. Protein data were statistically analyzed using the Kruskal-Wallis test, while beta-carotene and dietary fiber levels were analyzed using the one-way ANOVA test. Results: Glucomannan substitution did not affect protein content of baby porridge, while beta-carotene and dietary fiber levels increased significantly with porang glucomannan substitution. Conclusions: Porang glucomannan substitution had no effect on protein content but significantly increased beta-carotene and dietary fiber levels in Letelaku MPASI.